Mediators of Mast Cells in Bullous Pemphigoid and Dermatitis Herpetiformis - Zebrowska, Agnieszka; Wagrowska-Danilewicz, Malgorzata; Danilewicz, Marian; Stasikowska-Kanicka, Olga; Kulczycka-Siennicka, Lilianna; Wozniacka, Anna; Waszczykowska, Elzbieta (Mediators of Inflammation, 2014)
Bullous pemphigoid (BP) and dermatitis herpetiformis (DH) are skin diseases associated with inflammation. However, few findings exist concerning the role of mast cells in autoimmune blistering disease. Skin biopsies were taken from 27 BP and 14 DH patients, as well as 20 healthy individuals. Immunohistochemistry was used to identify the localization and mast cell expression of TNFα and MMP9 in skin lesions and perilesional skin. The serum concentrations of TNFα, MMP9, chymase, tryptase, PAF, and IL-4 were measured by immunoassay. TNFα and MMP9 expression in the epidermis and in inflammatory influxed cells in the dermis was detected in skin biopsies from patients. Although these mediators were found to be expressed in the perilesional skin of all patients, the level was much lower than that in lesional skin. Increased serum PAF levels were observed in BP patients. Mast cells may play an essential role in activating inflammation, which ultimately contributes to the tissue damage observed in BP and DH. Our findings suggest that differences in the pattern of cytokine expression directly contribute to variations in cellular infiltration in DH and BP.